Larga a motorized wheelchair mobility attachment for low-income, wheelchair-bound individuals to aid in long-distance wheeling - Lusung, Dean Gabriel C.
In recent years, there has been increasing recognition of the rights of people with disabilities, accompanied by the enactment of laws and movements aimed at promoting their inclusion and empowerment. However, the implementation of these laws and policies, particularly in developing countries like the Philippines, still faces significant challenges, resulting in a disparity among social classes and underserved communities, especially for individuals with mobility issues. This research study examines the landscape of mobility and accessibility for low-income wheelchair-bound individuals and highlights the barriers they face in accessing transportation and reaching their destination.